1993
DOI: 10.1111/j.1468-2338.1993.tb00666.x
|View full text |Cite
|
Sign up to set email alerts
|

Self‐employment: a study of seventeen OECD countries

Abstract: This article examines some institutional-political explanations for the revival of self-employment in seventeen OECD countries since the 1970s. The empirical analysis suggests that cross-country differences in the self-employment rate are partly explained by the generosity of unemployment insurance schemes, left party strength, the size of the state sector, as well as general economic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 17 publications
1
29
0
1
Order By: Relevance
“…Moreover, as self-employed workers often do not enjoy the same entitlement to benefits as those in waged employment, a high replacement ratio may also deter some workers from leaving paid-employment for self-employment for fear of losing their access to benefits. Both Staber and Bogenhold (1993) and Parker and Robson (2000) report evidence of a negative relationship between the replacement ratio and the rate of self-employment in the OECD.…”
Section: Analysis Of the Relationship Between Self-employment And Thementioning
confidence: 99%
“…Moreover, as self-employed workers often do not enjoy the same entitlement to benefits as those in waged employment, a high replacement ratio may also deter some workers from leaving paid-employment for self-employment for fear of losing their access to benefits. Both Staber and Bogenhold (1993) and Parker and Robson (2000) report evidence of a negative relationship between the replacement ratio and the rate of self-employment in the OECD.…”
Section: Analysis Of the Relationship Between Self-employment And Thementioning
confidence: 99%
“…Some authors have found robust influences of this variable on entrepreneurial behavior, for example Lucas (1978), Acs et al, (1994) and Klapper et al, (2010 A number of studies link this factor to business creation (Blanchflower, 2000), (Staber and Bogenhold, 1993) and (Cowling and Peter, 1997 and from a particular country in a specific year. The expectation here is that amount of compromised goods will have an impact on the number of businesses created in any given period.…”
Section: Control Variablesmentioning
confidence: 99%
“…Hence, the higher the replacement rate, the higher the opportunity cost of any form of employment versus non-employment (Duval 2003). Moreover, prior research suggests that higher unemployment benefits (Parker and Robson 2004;Staber and Bögenhold 1993) and access to pensions (Fuchs 1982;Zissimopoulos and Karoly 2007) discourage selfemployment compared to waged employment. Thus, if we equate benefits income with income from waged labour (ω t ) in the LM model, high benefits render the entrepreneurial option less desirable by increasing the attractiveness of its alternatives (ω t increases).…”
Section: Explanatory Variablesmentioning
confidence: 99%